2019
DOI: 10.1136/bmjopen-2018-028688
|View full text |Cite
|
Sign up to set email alerts
|

Labour room violence in Uttar Pradesh, India: evidence from longitudinal study of pregnancy and childbirth

Abstract: ObjectivesThe major objective of this study was to investigate the prevalence of labour room violence (LRV) (one of the forms of obstetric violence) faced by the women during the time of delivery in Uttar Pradesh (UP) (the largest populous state of India which is also considered to be a microcosm of India). Furthermore, this study also analyses the association between prevalence of obstetric violence and socioeconomic characteristics of the respondents.DesignThe study was longitudinal in design with the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 18 publications
1
27
2
Order By: Relevance
“…However, the proportion of OV in this study was higher than other previous studies’ report conducted in north Nigeria—55.9% [17], Kenya—20% [21], Brazil—18.3% [22], Northern India—28.8% [23] and Uttar Pradesh India—15.2% [24]. It was also higher as compared to studies done in Ethiopia such as pooled prevalence of systematic review and meta analysis—49.4% [25], Bahirdar city—67.1% [15], Southern Ethiopia—21.1% [26], four regions’ observational report—36% [27] and Northern Ethiopia—22% [16].…”
Section: Discussioncontrasting
confidence: 80%
“…However, the proportion of OV in this study was higher than other previous studies’ report conducted in north Nigeria—55.9% [17], Kenya—20% [21], Brazil—18.3% [22], Northern India—28.8% [23] and Uttar Pradesh India—15.2% [24]. It was also higher as compared to studies done in Ethiopia such as pooled prevalence of systematic review and meta analysis—49.4% [25], Bahirdar city—67.1% [15], Southern Ethiopia—21.1% [26], four regions’ observational report—36% [27] and Northern Ethiopia—22% [16].…”
Section: Discussioncontrasting
confidence: 80%
“…Another study assessing the association between disrespect and abuse and socio-demographic factors found that women of low socioeconomic status (SES) were over three times more likely (OR = 3.68; 95% CI = 1.4-9.7) to have experienced disrespect and abuse than those of high SES (Nawab et al, 2019). This aligns with findings from a longitudinal study in Uttar Pradesh, which found that rich women were nearly half as likely (OR = 0.65; 95% CI = 0.16-2.59) to experience 'obstetric violence' as poor women (Goli et al, 2019). In contrast, Diamond-Smith et al (2017) found that being in the richest (compared with the poorest) wealth quintile was significantly associated with reporting mistreatment during childbirth (OR = 3.268; p < 0.01).…”
Section: Stigma and Discrimination During Childbirthsupporting
confidence: 78%
“…A community-based study in Uttar Pradesh found that 84.3% of women reported some kind of disrespect and abuse (Nawab et al, 2019). While the prevalence of women reporting any form of 'obstetric violence' was about the same in the studies of Patel et al (2015) (57.7%), Sudhinaraset et al (2016) (57.0%) and Diamond-Smith et al (2017) (50.0%), other studies in Uttar Pradesh found a much lower prevalence of women reporting any kind of obstetric violencenamely, 28.8% (Bhattacharya & Sundari Ravindran, 2018) and 15.1% (Goli et al, 2019). The latter were closer to the findings from a facility-based survey by Dey et al (2017), where observational data by health care providers showed that 22.4% of women reported being mistreated during delivery.…”
Section: Harmful Traditional Practices and Beliefsmentioning
confidence: 67%
See 2 more Smart Citations